Hopfion-Driven Magnonic Hall Effect and Magnonic Focusing - Altbir-Drullinsky, D (American Physical Society, 2023)
Hopfions are localized and topologically nontrivial magnetic configurations that have received considerable attention in recent years. In this Letter, we use a micromagnetic approach to analyze the scattering of spin waves (SWs) by magnetic hopfions. Our results evidence that SWs experience an electromagnetic field generated by the hopfion and sharing its topological properties. In addition, SWs propagating along the hopfion symmetry axis are deflected by the magnetic texture, which acts as a convergent or divergent lens, depending on the SWs propagation direction. Assuming that SWs propagate along the plane perpendicular to the symmetry axis, the scattering is closely related to the Aharonov-Bohm effect, allowing us to identify the magnetic hopfion as a scattering center. © 2023 American Physical Society.